The shape of the liquid plain: sicilian salt flats - Felice Romano; Salvatore Damiano (Disegnare con)
<span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: IT; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This paper analyzes the salt flats as a place for the mixing of knowledge and experiences that originate and substantiate life: from the application of physical, chemical and biological principles to produce salt, to economic laws to regulate sales and trade, to aspects socio-anthropological aspects underlying the life of the communities that worked in production. A patrimony of material and immaterial overlaps, generated by the redesign of a segment of territory with physical and positional characteristics median between sea and land, and in which man strives to obtain fundamental resources for his livelihood. Given the complex moment of crisis and gradual abandonment that these particular ecological, anthropological and landscape systems are going through - in an attempt to avert the impending oblivion - the action of preserving this inestimable heritage could be restarted through an overturning of the consolidated reading key: evolve from the pervasion of the traditional taxonomic conception – or the intending of the landscape as a mediation between aesthetics and science - to arrive at an analysis, supported by the graphic-perceptive tools proper to the architect, of the traces left by human events on the territory. <span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: IT; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">DOI: https://doi.org/10.20365/disegnarecon.22.2019.20